Observations on sex differentiation in the oil palm, Elaeis guineensis L. - Williams, C.N.; Thomas, Roger L. (Oxford University Press, 1970)
The morphology and frequency of occurrence of abnormal hermaphrodite inflorescences in the oil palm is described for palms of varying age. Hermaphrodite inflorescences are manifest during changes of the sex cycle in the normally monoecious species, and gross morphological differences in the type of hermaphrodite inflorescences occurred depending on whether the change of cycle was from male to female or vice versa. The significance of the occurrence and morphology of the abnormal inflorescences is discussed in relation to the accumulation of photo-synthetic reserves and to the maturation process. © 1970 OXFORD UNIVERSITY PRESS.